Reconsidering children’s illness uncertainty and management experiences with female Japanese cancer survivors - Yamaguchi, Yu; Endo, Toshihiko (Frontiers in Psychology, 2022)
The aim of this study is to examine the illness uncertainties (IU) that children experience and the ways they manage them in order to construct a long-term, comprehensive developmental care for children with illness. Semi-structured, in-person interviews were conducted with six Japanese adolescent cancer survivors, all recruited from the same hospital in Tokyo, Japan. Using directed content analysis, all transcriptions that fell under the definition “the person is unable to construct the meaning of an illness related event of her/his self or another, and is aware of the state” were coded with the codes defined from the data, and which were then cross-referenced with the existing literature. The results indicated new aspects of children’s IU; uncertainties regarding hospitalization and the necessity to distinguish and examine IU with and without answers. In terms of IU management, we discuss the informative value “role models,” and depict how uncertainty acceptance may be a new form of solution.